Prevalence of otitis media with effusion among school going children in Bangladesh - Aich, Mani Lal; Biswas, Akhil Chandra; Ahmed, Miraj; Joarder, Md Abul Hasnat; Datta, Pran Gopal; Alauddin, M (Bangladesh Journal of Otorhinolaryngology, 2010)
A Prospective study was carried out from Jan 2000 Jan 2003, to find out the prevalence of OME among School children The study was done in Dhaka City and adjacent areas of Dhaka City in Savar, Munshigonj and Keranigonj, Altogether 280 Students aged 4-9 years were interviewed and examined. Nineteen percent children were found to have OME. In the urban community it was 17%, but in rural areas it was 21%. In our study children with OME were more in poorer people, smoker parents and bottle fed babies. Key words: Otitis media with effusion (OME), school children. DOI: 10.3329/bjo.v15i1.4308 Bangladesh J of Otorhinolaryngology 2009; 15(1): 31-34